Exercising body but not mind: A qualitative exploration of attitudes to combining physical activity and mindfulness practice for mental health promotion - Remskar, Masha; Western, Max J.; Maynard, Olivia M.; Ainsworth, Ben (Frontiers in Psychology, 2022)
Background: Physical activity and mindfulness meditation can be effective for maintaining good mental wellbeing, with early-stage research suggesting even greater effectiveness in tandem. Literature is lacking on the perceptions and acceptability of these practices, particularly in a preventative context. The study aimed to explore attitudes towards mental health and its maintenance through physical activity and mindfulness meditation in the university student population. Methods: Semi-structured qualitative interviews were conducted with a sample of 16 students from 10 UK universities (Mage=23 years, SD=3.22) recruited through social media and stratified to have varied wellbeing symptoms, physical activity levels and experience with mindfulness meditation. Reflexive thematic analysis was used to elicit meaning from the data. Results: Four main themes were constructed. Participants held a ‘Dualist view of health’, in which mental and physical aspects were seen as distinct but connected, and prioritised physical health maintenance. The ‘Low-point paradox’, where engagement is most difficult during the time of greatest need, was identified as a crucial psychological barrier across health behaviours. ‘Unfamiliarity with mindfulness practice’ was common, as were misconceptions inhibiting practice. Finally, participants were intrigued by combining physical activity and mindfulness, supposing that ‘Whole is greater than the sum of its parts’, with mutual reinforcement of the two techniques cited as the biggest motivating factor. Conclusions: Effective preventative mental health strategies for adults, including university students, should accommodate for common psychological barriers and facilitators to health maintenance behaviours, including misconceptions surrounding mindfulness, to increase acceptability. Combining physical activity and mindfulness meditation is one promising preventative approach that warrants further investigation.